Twenty Five Years Fighting for Women’s Health and Rights: Some Progress But Still a Long Way to Go - Temmerman, Marleen (Afrika Focus, 2019)
The aim of this paper is to provide an overview of 25 years women’s health and rights, a difficult journey with steps forward and backwards since the landmark conference in 1994 when reproductive rights were for the first time on the menu. However, although great strides have been made in reducing maternal and child mortality since then, among others by the United Nations with the establishment of the Millennium Development Goals for 2015, showing that change is possible, many countries are still lagging behind in reaching the goals. While the new global architecture, in particular with the Sustainable Development Goals and the Global Strategy for Women’s, Children’s and Adolescents’ Health, ensures that these issues remain high on the political agenda, this paper argues that we must move from political commitment to action, via the creation and dissemination of research evidence. As the Founding President of the Ghent Africa Platform (GAP) at Ghent University, I still believe GAP has an important role to play regarding this international collaboration and dissemination of scientific knowledge. KEYWORDS: WOMEN’S HEALTH, WOMEN’S RIGHTS, REPRODUCTIVE RIGHTS, UN DEVELOPMENT GOALS